YOU and YOUR CREDIT: Managing Your Credit - Joan P. Elmore; Michael S. Gutter; Travis P. Mountain (EDIS, 2008)
This document is FCS7231, part of the YOU and YOUR CREDIT series by Michael S. Gutter, Joan P. Elmore, and Travis P. Mountain. Published by the UF Department of Family Youth and Community Sciences, September 2008.